enCODE a feasibility study on the application of QR codes to automate data encoding - Baltao, Jocel Cathrine R.; De Leon, Dave Conrad H.; Iyo, Kayzee G.; Manalansan, Abegail D.
Expansion means more paperwork. New technology means new paperwork. Changing a business process means archiving paperwork. Paperwork is tantamount to inventory and is subjected to almost the same costs (e.g. stockroom). The invention of the computer meant that the use of paper is lessened but sometimes the amount of current paperwork is so great that it takes many months to transfer the old paperwork to the new computer system. For new paperwork it also meant having to type in lots of data during the time the paperwork is to be generated. A large company will hire people to type in all the paperwork data to a computer so that they can decrease the cost of having physical archives. Technology to simplify the transfer process was introduced many years ago but it can only accommodate but a fraction of the actual data that needs to be transferred. Recently a new potentially useful technology called the Quick Response code was developed in Japan. It is being used for applications not related to paperwork as of late. enCODE is a service provider that aims to combine that technology with the increasing need to transfer data into electronic archives without the hassle of having inaccurately encoded data and of having to wait long to finish encoding a set of paperwork data. Due to the nature of the QR code and the willingness of the potential customers to pay for a service provider like enCODE, the company has decided to cater to medium and large companies that have a significant amount of paperwork containing repetitive data. Two service packages will be offered and add-ons will be available too. Promotions will mostly entail newspaper ad listings and numerous publicity schemes to attract the bigger companies. From a financial standpoint, enCODE is a highly favorable investment with an ROI of 21 % in the first year and a payback period of two years. enCODE also requires a P4M investment and promises more than P17M in profits after five years. enCODE's services will also provide a means to lessen paper usage and thus helping the environment keep its trees standing for many years to come.